The Relationship of Bullying Behavior and Social Interaction in School-Age Children at SDN 22 Jambi City - Halijah, Halijah; Ekawaty, Fadliyana; Suryati, Suryati; Nasution, Riska Amalia; Imran, Suryadi (West Science Interdisciplinary Studies, 2024)
The problem that is currently widespread in education circles is bullying. The Organization for Economic Cooperation and Development (OECD) stated that Indonesia is ranked first in the position of bullying cases in ASEAN with 84% confirmed in 2023, and according to data from the Indonesian Child Protection Commission (KPAI) Bullying cases are quite a worrying issue in the school environment. Data records that there will be at least 1,478 cases of bullying reported in 2023. Bullying makes it difficult for children to interact well in their social environment and this can hinder the child's development process. This research was conducted to identify the relationship between bullying behavior and social interactions in school-age children at SDN 22, Jambi City. The research method used was quantitative research using a cross sectional approach. The research population was students of SDN 22 Jambi City grades IV, V, VI, totaling 103 samples taken using total sampling techniques. This research uses a questionnaire instrument. The analytical test used is Spearman Rho. The results of the research show that generally the bullying behavior data is in the low category of 96 respondents (93.2%) and most social interactions are in the good category of 80 respondents (77.7%). The test results obtained were (p 0.01<0.05). The conclusion is that there is a relationship between bullying behavior and social interaction in school-age children at SDN 22 Jambi City. It is hoped that the results of the research will be used as material for consideration by schools in providing guidance and counseling support services, so that students can understand the limits of social interaction.